Stability study of tubular DNA origami in the presence of protein crystallisation buffer1. Issue 72 (6th August 2015) - Wang, Dianming; Da, Ziran; Zhang, Bohan; Isbell, Mark Antonin; Dong, Yuanchen; Zhou, Xu; Liu, Huajie; Heng, Jerry Yong Yew; Yang, Zhongqiang
<x xml:space="preserve">Abstract</x> A method for screening compatible buffer conditions for both DNA origami and protein crystallisation and studied how protein crystallisation buffer conditions notably cations, buffering agents, precipitants, and pH, influenced the stability of tubular DNA origami.